The Role and Challenges of the Deputy Principal for Student Affairs in Developing Student Interests and Talents in High School - Aulia Salsa Nur Aqrima; Muhammad Wildan Shohib; Saddam Husein; Sifa Lutfiyani Atiqoh (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This research specifically aims to highlight the role and challenges of the deputy principal for student affairs in developing students' interests and talents in high school. The research was conducted at SMA Negeri 1 Simo Boyolali using a qualitative approach to highlight the role and challenges of the deputy principal for student affairs in developing students' interests and talents. Through in-depth interviews, it was found that the active involvement of the student affairs sector in student planning, managing new student admissions, and organizing extracurricular programs was the key to success. Obstacles such as limited finances and infrastructure are the main challenges faced. Support from the education department provides legitimacy and incentives for developing students' interests and talents. The implication is the need to increase innovation in education programs, improve the quality of facilities, and cross-sector collaboration to achieve quality and inclusive education for all students.